Strategic vision : America and the crisis of global power - Brzezinski, Zbigniew, 1928- (New York : Basic Books, 2013)
In 1991, the United States was the only global superpower. It seemed that the 21st century, like the 20th, would belong to America. Then came the stock market bubble, the costly foreign unilateralism of the younger Bush presidency, and the financial catastrophe of 2008. Meanwhile, China was rising and the Middle East was awakening politically. Today it is clear that America is vulnerable--to domestic and international decline and unregulated greed. Speaking from decades of experience, Brzezinski considers the implications of the changing distribution of global power, ponders why America's global appeal is waning, speculates on the likely geopolitical consequences if America declines by 2025 (will China assume America's central role in world affairs?), and describes a vision of a resurgent America: responsive to challenges, strategically deliberate, and historically enlightened in its global engagement with the new East.--Publisher description.
Part I. The receding West. The emergence of global power; The rise of Asia and the dispersal of global power ; The impact of global political awakening -- Part II. The waning of the American dream. The shared American dream ; Beyond self-delusion ; America's residual strengths ; America's long imperial war -- Part III. The world after America: by 2025, not Chinese but chaotic. The post-America scramble ; The geopolitically most endangered states ; The end of a good neighborhood ; The uncommon global commons -- Part IV. Beyond 2025: a new geopolitical balance. Eurasia's geopolitical volatility ; A larger and vital West ; A stable and cooperative new East -- Conclusion: America's dual role.
Includes bibliographical references (p. 195-196) and index.
BIGD
Keywords: Balance of power -- Forecasting; International relations -- History -- 21st century -- Forecasting; World politics -- 21st century -- Forecasting; Geopolitics -- Forecasting; United States -- Foreign relations -- 21st century -- Forecasting